Evaluasi Usability Pada Aplikasi PermataMobile X Dengan Menggunakan Metode Usability Testing Dan System Usability Scale(SUS) - Irdiaga Isnainrajab; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
PermataMobile X is an internet-based electronic banking service provided by PT Bank Permata Tbk (Permata Bank) for customers to access a transaction experience that is simple, fast, and reliable, easy to use and has a very complete transaction feature. Based on an interview with Mr. Bayu Ardhi Koencara as PermataMobile X Project Manager, and observations by researchers, there are still many usability issues in this application. This study was evaluated to measure the level of usability by using the Usability Testng Methid and The Usability Scale System thereby producing recommendations for improvement by measuring aspects of learning ability where the result is 68%. Calculation of these results are included in the category below the average., Aspects of effeciency of 0.01 goals / sec, the error aspect of 0.41. If the calculation results are compared with the standard errors that exist in each task that is 0.70 then the error is classified as below average. Satisfaction uses the System Usabilty Scale questionnaire to find out whether the user is satisfied with the system used which is filled by 20 active users and the results are on average 70.1. Participants of the test involved 5 users domiciled in Jakarta. Interviews were conducted to explore problems from the application so that they could be evaluated. Based on the results of usability testing and interviews found 4 problems. From these problems, recommendations for improvement were obtained according to usability guidelines